A Coupling of Voice and Iris Based Multimodal Biometric System for Person Authentication - Kale, Vijay K; Deshmukh, Prapti D (International Journal of Computer Sciences and Engineering, 2018)
Automatic human authentication by machine has been an active research area.This research work focus on development of Voice and Iris based Multimodal biometric system for human Authentication. The experimental work divided in three part, first and second part develop unimodel Voice and Iris biometric system and third experiment carried out for multimodal biometric fusion .we have achieve above form Multimodal biometric system results using KVKRG Voice and KVKR Iris database is FAR1.4% ,FRR 0.8%, Accuracy is 97.8%, ASV2015 voice and MMU Iris Database is FAR1.0% ,FRR 0.6%, Accuracy is 98.4% , Regional Voice Database and KVKR Iris database is FAR1.1% ,FRR 0.6%, Accuracy is 98.3%.